Documentation of Drug-Related Problems with ICD-11: Application of the New WHO Code-Set to Clinical Routine Data - Andrikyan, Wahram; Jung-Poppe, Lea; Altenbuchner, Anna; Nicolaus, Hagen Fabian; Pfistermeister, Barbara; Dormann, Harald; Fromm, Martin; Maas, Renke (Journal of Clinical Medicine, 2023)
Drug-related problems (DRPs), i.e., adverse drug reactions (ADRs) and medication errors (MEs), constitute a serious threat to the patient's safety. DRPs are often insufficiently captured by clinical routine documentation, and thus, they frequently remain unaddressed. The aim of this study was to assess the coverage and usability of the new 11th revision of the WHO International Classification of Diseases (ICD-11) to document DRPs. We refined the 'Quality and Safety Algorithm' from the ICD-11 Reference Guide and used it for DRP reporting to code 100 different anonymized DRPs (50 ADRs and 50 MEs) in a German hospital. The ICD-11 three-part model consisting of harm, cause, and mode was used whenever they were applicable. Of 50 ADRs, 15 (30.0%), such as drug-induced osteoporosis, were fully classifiable and codable by the ICD-11, whereas 35 (70.0%), such as drug-induced hypokalaemia, could not be fully classified due to sanctioning rules preventing the postcoordination (i.e., a combination of specific codes, such as drug and diagnosis). However, coding without the loss of information was possible in the 35 of these 35 (100.0%) ADR cases when we were deviating from the cluster code order of the Reference Guide. In all 50 MEs, the mode could be encoded, but for none of the MEs, postcoordination, i.e., the assignment of the ME to a specific drug, was allowed. In conclusion, the ICD-11 three-part model enables us to acquire more detailed documentation of DRPs than the previous ICD versions did. However, the codability, documentation, and reporting of DRPs could be significantly improved by simple modifications of the current ICD-11 sanctioning rules and by the addition of new ICD-11 codes.
CRIS-Team WoS Importer:2023-01-27
Keywords: drug-related problem; International Statistical Classification of Diseases and Related Health Problems; ICD-10; ICD-11; medication safety; medication error; adverse drug reaction; ADR; adverse drug event; ADE